Cooperation between distinct viral variants promotes growth of H3N2 influenza in cell culture - Xue, Katherine S; Hooper, Kathryn A; Ollodart, Anja R; Dingens, Adam S; Bloom, Jesse D (eLife, 2016)
RNA viruses rapidly diversify into quasispecies of related genotypes. This genetic diversity has long been known to facilitate adaptation, but recent studies have suggested that cooperation between variants might also increase population fitness. Here, we demonstrate strong cooperation between two H3N2 influenza variants that differ by a single mutation at residue 151 in neuraminidase, which normally mediates viral exit from host cells. Residue 151 is often annotated as an ambiguous amino acid in sequenced isolates, indicating mixed viral populations. We show that mixed populations grow better than either variant alone in cell culture. Pure populations of either variant generate the other through mutation and then stably maintain a mix of the two genotypes. We suggest that cooperation arises because mixed populations combine one variant’s proficiency at cell entry with the other’s proficiency at cell exit. Our work demonstrates a specific cooperative interaction between defined variants in a viral quasispecies.
Keywords: influenza; neuraminidase; D151G; cooperation; quasispecies; D151N